GERMINATION BEHAVIOR OF CASSIA TORA SEEDS IN VARIOUS PRE-SOWING TREATMENT METHODS - GEETIKA PANT; UGAM K. CHAUHAN (International Journal of Pharma and Bio Sciences, 2013)
Cassia tora seeds, like those of many leguminous species, have hard and impermeable coats. Germination is thought to be enhanced when seeds are scarified or soaked in concentrated sulfuric acid or hot water. This experiment shows the effect of various pre-sown treatments on C. tora with respect to its germination behavior. Germination percentages were significantly affected by different pretreatments in C. tora. A 24 h soaking after mechanical scarification showed a significant level of improved germination (76.88%) when compared to all other treatments. Acid treatment showed the same level of significant in germination percentage when the seeds were treated for 5 and 10 min. Though hot water treatment showed an increased percentage of germination at 50°C (44.54%), further increase in temperature drastically reduced the germination. Alcohol treatment did not show any significant increase in germination percentage when compared to control but reduced the germination at prolonged exposure.